2019
DOI: 10.1177/0361198119827904
|View full text |Cite
|
Sign up to set email alerts
|

Development and Assessment of a Connected Vehicle Training Program for Truck Drivers

Abstract: In Wyoming, because of the high likelihood of dangerous winter driving conditions, truck-related crashes on the freeway have resulted in remarkable fatalities, extended closures, and significant economic losses. The emerging connected vehicle (CV) technology has the potential to communicate road and traveler information to commercial truck drivers, which would eventually promote traffic safety. Nevertheless, currently there is a lack of a systems training program to deliver the CV technology to truck drivers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…CV-VSL Training. After the warm-up session, participants were provided with hands-on driving simulator training of VSL under CV environment (30). The CV-VSL driving simulator training scenario aims to provide participants training regarding how to take advantage of the CV system's advisory speed limits when driving under adverse weather conditions.…”
Section: Development Of Driving Simulator Testbedmentioning
confidence: 99%
“…CV-VSL Training. After the warm-up session, participants were provided with hands-on driving simulator training of VSL under CV environment (30). The CV-VSL driving simulator training scenario aims to provide participants training regarding how to take advantage of the CV system's advisory speed limits when driving under adverse weather conditions.…”
Section: Development Of Driving Simulator Testbedmentioning
confidence: 99%
“…This is in accordance with the Federal Highway Administration (FHWA)’s guidelines recommending the use of standard and easily recognizable signs, particularly those from the MUTCD for in-vehicle warning purposes ( 17 ). It is noteworthy that earlier research showed that professional truck drivers participating in the pilot’s education and training activities perceived the warnings as easy to understand ( 13 , 18 ).…”
Section: Methodsmentioning
confidence: 97%
“…Several studies have shown the significant benefits of CV technology in enhancing the traffic safety of drivers (28)(29)(30)(31)(32)(33)(34). A study showed that traffic safety could be increased by providing the appropriate driving speed using CV technology (35).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The E-training module included information about, followed by questions about, the introduction of CV technology and the Wyoming CV Pilot, different components of the CV system, the suite of the CV applications and notifications, and appropriate behaviors of drivers in response to notifications and warnings. This E-training module was an extension to the previously developed CV training program for truck drivers (28), but was modified to best suit the highway patrol troopers.…”
Section: E-training Modulementioning
confidence: 99%